Pendidikan Non Formal Sebagai Proses Penanaman Nilai-Nilai Islam Pada Anak - Mardiah Astuti; Vanessa R Iswandari; Novita Eka Sari; Dheista Galin; Mita Rolani; Ibrahim (Dirasah : Jurnal Studi Ilmu dan Manajemen Pendidikan Islam, 2023)
This article discusses non-formal education activities in the process of instilling Islamic values ​​in children at the Al-Qur'an Education Park in Kenten Laut Village. In the educational process it is carried out consciously and regularly, but does not really follow standard and firm rules. Non-formal education as a complement to informal and formal education for children. This study aims to determine how the process of non-formal education in inculcating Islamic values ​​in children. The type of research used is qualitative. Analysis of the data used in this study, namely interviews via Google form which serves to explore data or information related to the inculcation of Islamic values ​​in children in non-formal education. The results of this study are that some teachers at TPA Kenten Laut transfer Islamic values ​​to children, one of which is by teaching children the Koran and introducing Islamic aqidah from an early age. Things that can influence the inculcation of Islamic values ​​in children are parents and the surrounding environment. The impact of the inculcation of Islamic values ​​in children in non-formal education is that they can make children pious and pious and get good and right moral and religious values.